The Work-Ready Graduate Preparing Tomorrow's Workforce - Niman, Neil B.; Chagnon, Jennifer R. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book examines the tide of change facing higher education as it grapples with providing a more relevant and demonstrated value for its graduates entering the workplace. Based on their experience with the Business in Practice program they created, the authors share the rationale and practical approaches colleges and universities need to implement if they are to foster the development of a work-ready graduate. What sets the program apart are the two-credit courses crafted to take advantage of the unique knowledge and work experiences of industry professionals that complements our core curriculum. Utilizing experiential learning, the program is designed so that students can apply soft/smart skills in a progression that helps develop those capabilities that are beneficial for them and desired by employers. It is structured to bring internship-like experiences to campus, giving the vast majority of students a quality work-related experience that is impactful and relevant for today's economy. Neil B. Niman is currently the Faculty Director of the Business in Practice program at the University of New Hampshire, USA. He was previously the Associate Dean for Academic Programs and Chair of the Department of Economics where he holds a faculty appointment as Associate Professor of Economics. His previous book, The Gamification of Higher Education was also published by Palgrave Macmillan. Jennifer R. Chagnon is the Associate Director of Business in Practice at the Peter T. Paul College of Business and Economics at the University of New Hampshire, USA. She earned a BA in Business Management and Studio Fine Art from Juniata College and has over 15 years of experience in higher education, including in recruitment and enrollment management, academic affairs, and academic programming.
Introduction -- The Triple-Threat Graduate -- Purposeful Work -- Business in Practice -- Moving the Conversation Forward -- Where We End Up -- References -- Part I The Tide of Change -- Unrealized Opportunities -- A Series of Unrealized Opportunities -- Human Capabilities -- Self-Discovery -- Curriculum -- Connections -- Signals -- Technology -- A Way Forward -- References -- Human Capabilities -- Work-Related Intelligences -- Skills, Competencies, and Capabilities -- Twenty-First-Century Skills -- Storytelling: An Example -- The Future of Work -- Situational Awareness: An Example -- References -- Self-Discovery and Curriculum -- Self-Discovery -- General Education -- Reimagining General Education -- Key-Shaped Graduates -- Experiential Learning -- Cases -- Simulations -- Consulting Projects -- Internships -- Co-Op Programs -- Apprenticeship Programs -- Capabilities Across the Curriculum -- References -- Connections and Signals -- Connections -- Initiating Relationships -- Specialized Programming -- Signals -- Alternative Credentials -- Badging -- e-Portfolios -- A Communications Strategy -- References -- EdTech to the Rescue? -- Human Capabilities -- Self-Discovery -- Curriculum -- Connections -- Signals -- Is EdTech the Answer? -- References -- Part II Capitalizing on the Unrealized Potential -- Practice-Based Learning -- ISA2 -- Informal -- Situated -- Active -- Applied -- The Power of Guided Experiences -- Turning Skills Into Work-Ready Capabilities -- Situational Awareness-Being Attentive to One's Surroundings -- Storytelling-Crafting a Compelling Narrative -- Collaboration-Working Collectively to Advance a Shared Purpose -- Initiative-Knowing When and How to Take Action -- Adaptability-Responding to Changing Conditions and Circumstances -- Business in Practice -- The Role of Practice-Based Learning -- References -- Designing Learning Experiences -- Designing an Experiential Narrative: The STAR2 Approach -- Learning and Developmental Goals -- Example 1: Technology Procurement -- Example 2: Financial Narratives -- Example 3: Business Model Innovation -- Constructing the Learning Experience -- Example 4: Immersive Executive Experiences -- The Experience Arc -- Example 5: Product Licensing -- References -- Industry Professionals in the Classroom -- Opportunities for Professionals in the Classroom -- Recruiting Professionals -- Working with Industry Professionals -- Supporting the Learning Process -- Creating Community -- Active Learning and Encouraging Engagement -- Minimum Viable Information -- Guide Program -- Complements Rather than Substitutes -- References -- A Practice-Based Journey -- A Work-Ready Journey -- Gaming the System: A Student-Centered Design Approach -- The Best of All Possible Worlds -- Elevated Experiences -- Voice Z Digital -- Creating a Complementary Curriculum -- Realized Opportunities -- References -- Outcomes -- Assessment Planning -- Program Outcomes -- Program Elements -- Data and Methodology -- Assessment Map -- The Student Lens -- The Working Professional Lens -- The External Business Community Lens -- Continuous Improvement -- Assurance of Learning -- References -- Forces of Change -- Pathways of Change -- Seeds of Change -- Dynamics of Change -- All Aboard -- Open Up the Curriculum -- Craft Meaningful Experiences -- Welcome Working Professionals on Campus -- Create a Connected Community -- Embrace Innovation -- Agents of Change -- References.
Keywords: Education, Higher; Alternative Education; Career education; Continuing education; Professional education; Vocational education; Career development; Higher Education; Experiential Education; Career Skills; Lifelong Learning; Professional and Vocational Education; Careers in Business and Management